Problems in Cognitive-Behavioral Supervision: Theoretical Background and Clinical Application - Prasko, Jan; Abeltina, Marija; Krone, Ilona; Gecaite-Stonciene, Julija; Vanek, Jakub; Burkauskas, Julius; Liska, Roman; Sollar, Tomas; Juskiene, Alicja; Slepecky, Milos; Bagdonaviciene, Lina; Ociskova, Marie (Neuro-endocrinology letters, 2023)
Cognitive-behavioural therapists and trainees are encouraged to undergo supervision when offering therapy to troubled clients and to process personal attitudes and events likely to affect their therapeutic work. We discuss common problems in cognitive behavioural therapy (CBT) supervision, which may arise at the client, supervisee, or supervisor level. These issues include difficulties with case formulation, therapeutic strategies, and the therapeutic relationship. A supervisor can help their supervisee deal with clients with multifaceted or particularly challenging problems, such as difficulties with compliance, complex psychosocial problems, or chronic mental disorders. We also discuss matters related to the supervision process, the supervisor's role, different supervisory styles, and issues affecting a supervisee's feelings of vulnerability and shame. Furthermore, we analyze distinct supervision styles and potential problems arising from the supervision of experienced CBT therapists.
Keywords: kognitivně behaviorální terapie; Cognition; emoce; kognice; Emotions; lidé; Cognitive Behavioral Therapy; Humans